Born blonde: a recessive loss‐of‐function mutation in the melanocortin 1 receptor is associated with cream coat coloration in Antarctic fur seals. Issue 16 (22nd July 2016) - Peters, Lucy; Humble, Emily; Kröcker, Nicole; Fuchs, Birgit; Forcada, Jaume; Hoffman, Joseph I.
Abstract: Although the genetic basis of color variation has been extensively studied in humans and domestic animals, the genetic polymorphisms responsible for different color morphs remain to be elucidated in many wild vertebrate species. For example, hypopigmentation has been observed in numerous marine mammal species but the underlying mutations have not been identified. A particularly compelling candidate gene for explaining color polymorphism is the melanocortin 1 receptor ( MC1R ), which plays a key role in the regulation of pigment production. We therefore used Antarctic fur seals ( Arctocephalus gazella ) as a highly tractable marine mammal system with which to test for an association between nucleotide variation at the MC1R and melanin‐based coat color phenotypes. By sequencing 70 wild‐type individuals with dark‐colored coats and 26 hypopigmented individuals with cream‐colored coats, we identified a nonsynonymous mutation that results in the substitution of serine with phenylalanine at an evolutionarily highly conserved structural domain. All of the hypopigmented individuals were homozygous for the allele coding for phenylalanine, consistent with a recessive loss‐of‐function allele. In order to test for cryptic population structure, which can generate artefactual associations, and to evaluate whether homozygosity at the MC1R could be indicative of low genome‐wide heterozygosity, we also genotyped all of the individuals at 50 polymorphic microsatellite loci. We were unable to detect any population structure and also found that wild‐type and hypopigmented individuals did not differ significantly in their standardized multilocus heterozygosity. Such a lack of association implies that hypopigmented individuals are unlikely to suffer disproportionately from inbreeding depression, and hence, we have no reason to believe that they are at a selective disadvantage in the wider population. Abstract : We sequenced the melanocortin 1 receptor ( MC1R ) of 70 wild‐type and 26 cream‐coloured Antarctic fur seals and identified a recessive loss‐of‐function mutation clearly associated with cream coat colour. In order to evaluate whether homozygosity at the MC1R could be indicative of low genome‐wide heterozygosity, we also genotyped all individuals at 50 polymorphic microsatellite loci and found no difference in standardized multilocus heterozygosity between wild‐type and cream‐coloured individuals. Such a lack of association implies that hypopigmented individuals are unlikely to suffer disproportionally from inbreeding depression and thus do not appear to be at a selective disadvantage in the wider population.